Tissue imaging using nonlinear laser scanning microscope - Lam, Edward Jin Cheong (2018)
The human eye consists of many complex layers and microstructures that interact with one another to bring about vision. Recently, there is a need to visualize the various components inside the eye to help in the identification, diagnosis and treatment of eye diseases [1]. Currently, non-linear optical technology is explored to image the eye structures. One such technology for visualization is called two photon microscopy which uses the concept of Two Photon Excitation and has similarities to Confocal Laser Scanning Microscopy. The two photon microscopy is done via detection of autofluorescence signals present inside the retina cells. For this project, its aims were to understand the principles of light, fluorescence and non linear optics and how is it applied into various functions and parameters used in two-photon microscopy to image the various retina microstructures of different bovine retina samples. The project also looks at the various challenges faced when using Confocal Laser Scanning Microscopy to image the 2-dimensional and 3-dimensional structures of the bovine retina.